Altitude and decomposition stage rather than litter origin structure soil microarthropod communities in tropical montane rainforests. (October 2018) - Marian, Franca; Sandmann, Dorothee; Krashevska, Valentyna; Maraun, Mark; Scheu, Stefan
Abstract: Microarthropods impact organic matter turnover and nutrient cycling via processing of organic matter entering the soil as litter and root exudates. Variations in the structure of soil microarthropod communities are due to both biotic and abiotic factors such as local climatic conditions and litter quality. However, in particular in tropical ecosystems the relative importance of these factors for structuring soil microarthropod communities are little understood. We investigated variations in the structure of soil microarthropod communities in leaf and root litter from three altitudes exposed in three tropical montane rainforests at different altitude in southern Ecuador for three years. Leaf litter from three abundant tree species and roots of different diameter were collected from three sites at different altitude (ca. 1000, 2000, 3000 m). Litter and roots were placed in litterbags at the three altitudes, and after 6, 12, 24 and 36 months soil microarthropods in the litterbags were analysed. Density of Acari and Collembola, and diversity of Oribatida decreased with increasing altitude and varied with the degree the litter was decomposed rather than with litter origin and therefore quality of the litter material. Densities fluctuated during litter decomposition generally being lowest after 24 months but higher after 36 months. Species composition of Oribatida varied strongly with altitude; only few species overlapped between altitudes. The percentage of parthenogenetic Oribatida species decreased with increasing altitude. The results suggest that the origin and therefore quality of litter material is of little importance as driving factor for the composition of microarthropod communities of tropical montane rainforests. Factors changing between rainforest sites at different altitude, as well as decomposition stage of litter and associated changes in the microbial community are much more important. Highlights: Altitude and decomposition stage are crucial drivers of microarthropod communities. Litter quality little affects microarthropods in tropical montane rainforests. Microarthropods do not profit from favourable conditions during early decomposition. Microarthropods are more abundant and drivers at late stages of decomposition. Importance of litter-derived resources as food source changes during decomposition.